Increasing Use of Anticoagulants in Germany and Its Impact on Hospitalization for Tooth Extraction - von Beckerath, Olga; Kröger, Knut; Santosa, Frans; Nasef, Ayat; Kowall, Bernd; Stang, Andreas (Hämostaseologie, 2021)
Objectives This article aimed to compare nationwide time trends of oral anticoagulant prescriptions with the time trend of hospitalization for tooth extraction (TE) in Germany from 2006 through 2017.Patients and Methods We derived the annual number of hospital admissions for TE from the Nationwide Hospital Referral File of the Federal Bureau of Statistics and defined daily doses (DDD) of prescribed anticoagulants in outpatients from reports of the drug information system of the statutory health insurance.Results From 2005 to 2017, annual oral anticoagulation (OAC) treatment rates increased by 143.7%. In 2017, direct oral anticoagulants (DOACs) represented 57.1% of all OAC treatments. The number of cases hospitalized for TE increased by 28.0 only. From all the cases hospitalized for TE in Germany in 2006, 14.2% had a documented history of long-term use of OACs. This proportion increased to 19.6% in 2017. Age-standardized hospitalization rates for all TE cases with long-term use of OACs increased from 6.6 in 2006 to 10.5 cases per 100,000 person-years in 2014 and remained almost unchanged thereafter.Conclusion Our comparison showed that the large increase in OAC treatment rates in general from 2006 to 2017 had only a small impact on hospitalized TE cases with long-term use of OAC which flattens since 2014.
Keywords: tooth extraction; vitamin K antagonists; direct oral anticoagulants; bleedings